HUBUNGAN ANTARA KECEPATAN DAN DAYA LEDAK DENGAN PRESTASI LARI 100 METER - Darni FIK-UNP (Pusat Kajian Pendidikan Olahraga Kesehatan Rekreasi, 2016)
The problem of this research is that short distance sprint (100 m) of male students of FIK UNP Padang is influenced by their speed reaction and explosive power either partially or simultaneously. The amount of the population was 415 students in academic year of 2004. to run it well, the researcher used proportional stratified Random Sampling to which the students of the same level was grouped by 25% of which. According to the exist data that there were 92 students could be analyzed. The instruments used were: (1) measuring the Speed Reaction. As the result, the rank of validity of the test in for the Reliability of the test was 0,84; (2) Standing Broad Jump Test of which the Explosive Power was measured. The result of this test showed the validity of 0,61 and the Reliability was 0,96; (3) Sprint 100 m test used stopwatch for measured the 100 m Run Achievement. From this research the correlations found were: (1) There was a significant correlation between the Speed Reaction with 100 m Run Achievement: (2) There was a significant correlation between the Explosive Power with the 100 m Run Achievement; (3) There was a signficant correlation among the Speed Reaction and the Explosive Power with the 100 m Run Achievement.